Vitamin C Intake Adequacy and the Incidence of Anemia in Pregnant Women - Anisa Dwirizky Abdullah; Sukma Yunita; Nur Zakiah (Journal of Global Nutrition, 2026)
Anemia during pregnancy constitutes a major public health concern in Indonesia, with inadequate micronutrient intak, particularly vitamin C, identified as a key contributing factor. Vitamin C (ascorbic acid) facilitates the absorption of non-heme iron, thereby playing a critical role in hemoglobin synthesis. This study aimed to examine the relationship between vitamin C intake adequacy and the incidence of anemia among pregnant women in the working area of Puskesmas Totoli, Majene Regency, West Sulawesi. A cross-sectional observational design was employed, involving 106 pregnant women in the first and second trimesters selected via simple random sampling. Dietary assessment was conducted using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), hemoglobin levels were measured using the Easy Touch GCHb digital device, and anemia was defined based on the Indonesian Ministry of Health criteria (Hb <11 g/dL for trimesters I and III; <10.5 g/dL for trimester II). Results indicated that 34.9% of subjects were anemic, and 46.2% had inadequate vitamin C intake (mean: 57.18 mg/day; AKG 2019 recommendation: ≥95 mg/day during pregnancy). Among subjects with inadequate vitamin C, 51.0% were anemic, compared to 21.1% among those with adequate vitamin C. Bivariate analysis using the Chi-square test revealed a statistically significant association between vitamin C adequacy and the incidence of anemia (p = 0.001). These findings underscore the importance of improving vitamin C consumption through fruit, vegetable, and dietary diversification programs to support iron absorption and reduce anemia risk during pregnancy